2019
DOI: 10.2147/dmso.s204836
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association between glycemic status and thyroid dysfunction in patients with type 2 diabetes mellitus</p>

Abstract: Background Thyroid dysfunction has been widely reported to be more common in patients with type 2 diabetes mellitus (T2DM) in various parts of the world; however, there is paucity of data on this in our environment. Objective The aim of this study was to determine the possible relationship between glycemic status and thyroid dysfunction. Methodology A total of 354 T2DM patients and 118 non-diabetic persons (controls) were recruited for the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 26 publications
0
27
2
Order By: Relevance
“…Diabetic patients with hypothyroidism are susceptible to periodic hypoglycemic episodes. In addition, severe hyperthyroidism may lead to hyperglycemia [ 86 , 87 , 88 ]. Reports suggest that diabetic individuals are more likely to develop thyroid nodules [ 89 ].…”
Section: Disorders and Diseases Associated With Thyroid Dysfunctionmentioning
confidence: 99%
“…Diabetic patients with hypothyroidism are susceptible to periodic hypoglycemic episodes. In addition, severe hyperthyroidism may lead to hyperglycemia [ 86 , 87 , 88 ]. Reports suggest that diabetic individuals are more likely to develop thyroid nodules [ 89 ].…”
Section: Disorders and Diseases Associated With Thyroid Dysfunctionmentioning
confidence: 99%
“…In addition, ICU patients with ESS tend to experience more severe symptoms compared to those with normal thyroid function [8]. Thyroid dysfunction occurs more often in diabetic patients relative to the general population while poor glycemic control coincides with a lower level of free T3 (FT3) in serum [9]. ESS in children with T1DM results in poor metabolic control and ketoacidosis [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…56 Several studies showed an inverse relationship between serum FT3 and HbA1c, and a positive relationship between TSH and HbA1c in the T2DM patients that could be attributed to the effect of prolonged hyperglycemia on the peripheral deiodination of T4 to T3. 33,34,57 These studies indicate that blood glucose, particularly HbA1c, can affect thyroid hormones. Thus, strict glycemic control can improve thyroid function and even correct thyroid hormone abnormalities without the need for thyroid dysfunction treatment.…”
mentioning
confidence: 99%